Attractiveness of essential oils of three Cymbopogon species to Tribolium castaneum (Herbst) adults - Đukić, Nikola; Radonjić, Anđa; Andrić, Goran; Kljajić, Petar; Drobac, Milica; Omar, Eihab; Kovačević, Nada (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
Behavior bioassays were conducted in the laboratory (23 ± 1ºC and 50 ± 5% r.h.) using the olfactometer to determine the effects of essential oils of three plant species in the Cymbopogon genus (Lemongrass), Cymbopogon nervatus, C. proximus and C. schoenanthus, on adults of Tribolium castaneum. The effect of essential oils was compared to a commercial biopesticide based on azadirachtin at three concentrations (0.0001, 0.001 and 0.01%). The results showed that all essential oils and the azadirachtin-based biopesticide had significant (p <0.05) repellent effects on T. castaneum adults at all tested concentrations, except C. proximus essential oil which showed a neutral effect at the lowest concentration. The highest concentrations of the essential oils of C. nervatus and C. proximus had significantly stronger repellent effects (p <0.05) than the lowest concentration. At the concentrations of 0.0001 and 0.001% all tested essential oils and azadirachtin showed a similar repellent effect without statistically significant difference, whereas the oil of C. nervatus had the highest repellent effect on adults of T. castaneum at the 0.01% concentration. Considering all tested variations, the essential oils of plants of the genus Cymbopogon showed similar or stronger repellent effects on T. castaneum adults than the biopesticide based on azadirachtin.